THE BEHAVIOR OF BANKERS TOWARDS PROFIT AND LOSS SHARING CONTRACTS: A Modified Theory of Planned Behavior Approach - Agriyanto, Ratno; Fatoni, Nur; Fuadi, Nasrul Fahmi Zaki; Irfan, Mohammad; Husnurrosyidah, Husnurrosyidah (Ulul Albab: Jurnal Studi Islam, 2022)
This paper aims at determining the psychological factors of bankers in implementing Profit and Loss Sharing (PLS) financing contracts in Islamic banks. The phenomenon of low occurrence of PLS financing motivated the researcher to write this paper. The theory of modified planned behavior is used to explain the research problem. The research data were obtained from 139 employees of Islamic banks in Indonesia and processed using SEM-PLS. The results show that trust has an effect on attitudes; subjective attitudes and norms affect intentions; perceived behavioral control has no effect on intention and behavior; intention influences behavior; and the perception of inefficiency has a negative effect on the relationship between intention and behavior. This paper contributes to the elaboration of the psychological factors affecting the behavior of bankers in implementing PLS. The implications of this paper for designing the strategies to improve the bankers' behavior in PLS financing are: the management must boost the bankers' confidence for the PLS financing benefits; the stakeholder’s social pressure is needed; the authority of bankers in implementing PLS financing needs to be increased; the bankers' access to the partner’s financial reports needs to be expanded; and the regulators need to give appreciation to Islamic banks that have a larger PLS portfolio.